Dali's optical illusions /. - Ades, Dawn; Dalí, Salvador, 1904-1989 (Yale University Press, 2000)
Published to accompany the exhibition held at the Wadsworth Atheneum Museum of Art Hartford, Connecticut, January 21 - March 26, 2000